Appraisal of the Genus Pleurastrum (Chlorophyta) Based on Molecular and Climate Data - Katia Sciuto; Marion A. Wolf; Michele Mistri; Isabella Moro (Diversity, 2023)
Two green microalgal strains, CCCryo 469-16 and CCCryo 470-16, were isolated from samples of Antarctic microflora. Their morphology and 18S rRNA sequences indicated a phylogenetic relationship with strains of the genera Chlorococcum Meneghini, Macrochloris Korshikov, and Pleurastrum Chodat. The last genus is considered particularly problematic as it underwent several revisions. Moreover, its type strain, P. insigne SAG 30.93, was recently demonstrated to coincide genetically with the authentic strain of Chlorococcum oleofaciens from an 18S rRNA phylogeny. This deprived the genus Pleurastrum of an important type reference. Thus, the molecular markers rbcL, tufA, and ITS were employed to identify the Antarctic isolates more precisely. Several other microalgae related to our isolates were obtained from international culture collections for comparison. The obtained results allowed the re-establishment of strain P. insigne SAG 30.93 as the reference strain and the definition of the molecular borders of both genera Pleurastrum and Chlorococcum. Based on our findings, several Chlorococcum species are now re-attributed to Pleurastrum, as well as Macrochloris rubrioleum, here re-named Pleurastrum rubrioleum comb. nov., to which the Antarctic isolates also belong. Finally, a relationship between Pleurastrum lineages and climate zones was established.